Clinicopathological Study Of Actinomycotic Mycetomas - Sentamilselvi G; Selvam A; Janki C; Kamalam A; Janaki V.R (Wolters Kluwer Medknow Publications, 1999)
Seventeen cases of actinomycotic mycetoma caused by actinomadura madurae, nocardia spp. And A. pelletierii has been described. Actinomadura madurae was the commonest organism (ten) detected followed by norcardia spp. (four) and A. pelletierii (three). Males were commonly involved. Large soft white grains of A. madurae and small firm red grains of A. pelletierii were consistently seen. Histopathological examination was diagnostic in all the cases showing grains with scalloped margin with pale center and deeply stained periphery with prominent eosinophilic club in A. madurae, deep stained grain with smooth margin and horizontal cracks in A. pelletierii and the pale stained small grain of other norcardia spp. Bone involvement varied from osteolytic to osteosclerotic changes. Actinomadura madurae commonly involved the feet which was by far the commonest site of mycetoma. Combined drug regimens like streptomycin along with cotrimoxazole and amikacin with cotrimaxazole were found to be effective in cases of mycetoma due to A. Pelletierii. Norcardia spp. Responded well to the oral cotrimoxazole given as a monotherapy. The need to start the patient on multi-drug therapy in cases of A. pelletierii and A. madurae especially with bone involvement is stressed. Rare sites like antecubital, popliteal fossae, posterior aspect of trunk, shin and scalp were also involved by actinomycotic species.